Movement patterns of blue swimming crab, Portunus pelagicus in the Sarawak coastal water, South China Sea - Mohd., Ikhwanuddin; A. H, Nurfaseha; A.B., Abol-Munafi; M. L., Shabdin (Journal of Sustainability Science and Management, 2012)
A study was carried out to determine the movement patterns of P. pelagicus within the near-shore marine embayment of the Sarawak coastal water, South China Sea. These mark-recapture tagging studies were conducted for about five months from 26th March till 30th August 2005 comprising 48 sampling trips. Out of 976 crabs tagged and released, 212 (21.72%) were recaptured. The mean distances moved by male and female crabs were 7.36 km ± 1.78 and 9.15 km ± 1.87 respectively. The study shows that the female crabs moved significantly (p=0.01; p<0.05) further than males. The percentage of tagged crabs recaptured within the original release site were 50.0% for male and 45.83% for female crabs. The result shows that the male crabs only significantly (p=0.01; p<0.05) moved towards the deeper off-shore areas as compared to the near-shore areas. On the other hand, the female crabs moved significantly more towards both deeper off-shore and shallow near -shore areas. Most of the tagged crabs were recaptured within the sampling site of 2 km radius after a minimum of 30 days at liberty. The movement activities from the study were not necessarily limited because only 21.72% of the tagged-and-released crabs were recaptured. Thus, the main movement activities were attributed to the migration movements associated with reproduction and this can be seen from the tagged crabs which were recaptured at the off-shore deeper water.